A pragmatic parallel group implementation study of a prehospital-activated ECPR protocol for refractory out-of-hospital cardiac arrest. (October 2021) - Grunau, Brian; Bashir, Jamil; Cheung, Anson; Boone, Robert; McDonald, Ken; Scheuermeyer, Frank; Singer, Joel; Jenneson, Sandra; Straight, Ron; Twaites, Brian; Harris, Luke; Haig, Scott; et al.
Abstract: Objectives: Extracorporeal membrane oxygenation within CPR (ECPR) may improve survival among patients with refractory out-of-hospital cardiac arrest (OHCA). We evaluated outcomes after incorporating ECPR into a conventional resuscitation system. Methods: We introduced a prehospital-activated ECPR protocol for select refractory OHCAs into one of four metropolitan regions in British Columbia. We prospectively identified ECPR-eligible patients in both the ECPR region and the three other regions to serve as the control group. We compared the proportion with favorable neurological outcomes at hospital discharge (cerebral performance category ≤ 2) and used logistic regression to estimate the association with treatment region. Results: The study was terminated prematurely due to changes in hospital protocols and COVID-19. In the ECPR region, 15/58 (25.9%) patients had favourable neurological outcomes owing to conventional resuscitation and 2/58 (3.4%) owing to ECPR, for a total of 17/58 (29.3%). In the control regions, 67/250 (26.8%) patients had a favourable outcome owing to conventional resuscitation, for a between-group difference of 2.5% (95% CI −10 to 15%). We did not detect a statistically significant association between treatment region and outcomes. Conclusion: In this prematurely-terminated study of ECPR for refractory OHCA, we did not detect an association between a regional ECPR protocol and neurologically favorable outcomes. However, our data suggests that outcomes owing to conventional resuscitation were similar, with the potential for additional survivors due to ECPR therapies.